Democracy Unbound: Introduction to Papers on Global Democracy - Joakim Nergelius (Oñati Socio-Legal Series, 2011)
There is no doubt whatsoever that the papers presented in this volume cover a very wide, even extensive range of topics. This is of course logical, given the multi-disciplinary nature of this scientifical project.  Nevertheless, it is a pleasure to present no less than eight papers devoted to new results and ideas in fields as diverse as psychology, philosophy, political science and law, dealing with matters such as electoral behavior, globalization, the concept of democracy, the role of experts or the relevance of thinkers such as Plato and Hobbes for the current discussion on the EU constitution. DOWNLOAD THIS PAPER FROM SSRN: http://ssrn.com/abstract=1837316